Comments on the amateur creation of passeriformes and its control system: SISPASS - Lorieri, V. C.; Robis, F. N. M. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Since the 1960s, to keep wild animals at home, as a pet, it must be of legal origin (VILLE, 2012). The control method of wild animals origin is based on marking devices, which must be linked to the original document, usually represented by purchase bills. However, there is an activity in Brazil that doesn’t comply the general rule. It is the amateur creation of wild passerine birds, stated in 1967’s Federal Law nº 5.197 (BRASIL, 1967), and currently regulated by the 2010’s Ibama Normative Instruction nº 10 (INSTITUTO BRASILEIRO DO MEIO AMBIENTE E DOS RECURSOS NATURAIS RENOVÁVEIS, 2011). For managing this activity, a computerized system had to be created, named the Passeriform Registration System (Sispass). This system consists of a database, created in 2003, which includes all the information from Brazilian amateur breeders (ROSA et al., 2003), who must keep their records up to date, routinely stating the situation of their respective breed. This system operates on-line and was created to manage and supervise passerine breeders. These peculiarities wouldn’t be justified by the established general rules for the maintenance of wild animals in captivity; however, it is observed that the purpose of this activity, called an amateur creation of passerines, isn’t merely keeping the animals in captivity. It aims to maintain a culture of passerine breeding, making it a legal activity (ROSA et al., 2003).